Calorimetric measurements of the destabilisation of a ribosomal RNA hairpin by dimethylation of two adjacent adenosines. - Heus, H A (1983)
Fragments of 16S ribosomal RNA from E. coli and B. stearothermophilus, respectively comprising the 49 and 52 3' terminal nucleotides have been studied thermodynamically using high sensitivity differential scanning calorimetry. The fragments were isolated after cleavage of 16S rRNA in the ribosome by the bacteriocin cloacin DF13. Comparison of the thermal properties of the E. coli fragments with those derived from a kasugamycin resistant mutant, which specifically lacks dimethylation of two adjacent adenosines was employed to study the effect of the methylgroups on the thermal stability. Both E. coli species exhibit similar complex melting patterns with several transitions. Overall molar transition enthalpies are equal and do not depend significantly on buffer conditions (120 kcal/mol at 15 mM Na+ to 136 kcal/mol at 215 mM Na+). However, the transition with the highest Tm, corresponding to unfolding of a nine basepair central helix is lowered by the dimethylation of the adenines in the four-membered loop. This decrease amounts to 4 degrees C at 15 mM Na+ and 2 degrees C at 215 mM Na+. The corresponding nine basepair long hairpin in the Bacillus fragment melts at a temperature of 70 degrees C at 15 mM Na+. This Tmax is much higher than expected on the basis of the sequence in the hairpin.